The Oxford handbook of German politics - Larres, Klaus; Moroff, Holger; Wittlinger, Ruth (Oxford University Press, 2022)
Few countries have caused or experienced more calamities in the 20th century than Germany. The country emerged from the Cold War as a newly united and sovereign state, eventually becoming Europe's indispensable partner for all major domestic and foreign policy initiatives. This handbook provides a comprehensive overview of some of the major issues of German domestic politics, economics, foreign policy, and culture by leading experts in their respective fields. This book serves primarily as a reference work on Germany for scholars and an interested public, but through this broader lens it also provides a magnifying glass of global developments which are challenging and transforming the modern state. The growing importance of Germany as a political actor and economic partner makes this endeavor all the more timely and pertinent from a German, European, and global perspective.
Enthält Literaturangaben und ein Register
Literaturangaben
Keywords: Germany -- Politics and government; Aufsatzsammlung; Politik; Deutschland